Substitusi Agregat Halus Dengan Serbuk Kaca Terhadap Kuat Tekan dan Kuat Lentur Beton dengan Penambahan Zat Epoxy - Rino Dwi Laksono; Syahrul Sariman; Arman Setiawan (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The construction world has developed very quickly in recent years. Concrete is one example. Over time many new innovations have emerged to strengthen the concrete itself and the means of reducing waste that exist in the community. The purpose of this study was to obtain the influence of partial substitution of sand with glass powder by 40%, 50%, 60% and the addition of epoxy substances by 10% on thestrength of concrete bending press. 44 samples were made, including 20 normal concrete samples and 24 variation concrete samples. Concrete will be soaked for 28 days. Testing of compressive strength, and bending strength of concrete is carried out when the life of the test object reaches 28 days. The results of this test show that variation concrete has a compressive strength, and a higher bending strength of concrete than normal concrete. The more use of glass powder on the concrete mixture, the more decreased the compressive strength, and the strength of its lentur. However, the compressive strength and flexural strength of variation concrete are still higher than the normal compressive and flexural strength of concrete. Epoxy does not have a great impact on concrete containing glass powder.